The Cross-Section of Expected Returns: Where We Stand Today - Karolyi, G. Andrew (Review of Financial Studies, 2016)
The Review of Financial Studies has among its missions the facilitation and promotion of a vigorous academic debate across unsettled questions in finance. This special section of Volume 29, Number 1 consists of three studies on the cross-section of expected returns. To what extent are our inferences about certain anomalous patterns in the cross-section of expected returns related to biases and inefficiencies in our testing procedures? Are all factor discoveries equally important? Do some proposed factors subsume the explanatory power of others? Is the after-trading-cost performance of some anomalies more resilient than that of others?